(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Immune-mediated microvascular thrombosis (IMMT) is a complex disorder driven by immune dysregulation, leading to microvascular occlusion and necessitating anticoagulant therapy. This study evaluates the impact of anticoagulant therapy on hemostatic parameters (D-dimer, fibrinogen, prothrombin time [PT], activated partial thromboplastin time [APTT]) and inflammatory markers (C-reactive protein [CRP], interleukin-6 [IL-6]) in 45 patients with IMMT. Patients were followed for 12 months, receiving either warfarin or direct oral anticoagulants (DOACs). D-dimer levels decreased significantly (1.5 µg/mL to 0.6 µg/mL, p<0.01), with DOACs showing greater reduction (p=0.02). Fibrinogen remained elevated in 60% of patients (mean 4.3 ± 0.9 g/L), correlating with CRP (r=0.65, p<0.01). IL-6 levels declined from 12.5 pg/mL to 5.8 pg/mL (p<0.05), reflecting reduced inflammation. Thrombotic recurrence occurred in 18% of patients, associated with persistent fibrinogen elevation (OR 2.9, 95% CI 1.1–7.6, p=0.03). These findings highlight the role of hemostatic and inflammatory markers in monitoring therapy efficacy and predicting outcomes in IMMT, supporting personalized treatment approaches.